Analysis of Terpolymerization Systems for the Development of Carbon Fiber Precursors of PAN - Daniel Alcalá-Sánchez; Juan-Carlos Tapia-Picazo; Adrian Bonilla-Petriciolet; Gabriel Luna-Bárcenas; J. M. López-Romero; Alberto Álvarez-Castillo (International Journal of Polymer Science)
The thermal stabilization of polyacrylonitrile fibers (FPAN) is one of the most important steps in the production of carbon fibers (CFs). In this paper, new precursor polymers from PAN have been synthesized with different chemical characteristics using a solution polymerization, and FPAN was obtained using an unconventional wet spinning system in the drying and collapsing steps. The effect of different operation conditions, comonomers, and termonomers on the properties of precursor polymers, polymerization reactions, mechanical properties, structural characteristics, and stabilization of the FPAN was studied and analyzed. FTIR and optical microscopy were used to analyze structural changes of FPAN in the thermal stabilization. The impact of the chemical composition of the precursor polymers on the physicochemical characteristics of FPAN and their behavior in the thermal stabilization process were evaluated. In particular, itaconic acid termonomer improved the tensile strength of the fibers from 8.07 to 16.87 cN/dtex, and the extent stabilization increased from 1.81 to 4.6. FTIR indicated that the reaction of stabilization of the terpolymer developed was initiated at a lower temperature compared to that of a commercial precursor polymer.